PENERAPAN STRATEGI PETA KONSEP LABA-LABA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IV SD NEGERI 2 TANAH ABANG - Rini Hartini; Kiki Aryaningrum; Ida Suryani (Universitas Negeri Medan, 2022)
Abstract : The Implementation of the Profit Concept Map Strategy on Student Learning Outcomes in Social Studies Subject Class IV SD Negeri 2 Tanah Abang. This research was conducted by researchers intending to find out 1) significant differences in learning outcomes of fourth grade students at SD Negeri 2 Tanah Abang who were taught using a spider concept map on learning outcomes 2) Application of the spider concept map strategy on student learning outcomes in subjects Social Studies class IV SD Negeri 2 Tanah Abang. This study applies the experimental method, which is a test in the form of a questionnaire with 15 questions, and a Quasi Experiment Design sheet with a Nonquivalent Control Group Design form. The sample in the context of this study consisted of two classes, the experimental class which consisted of 30 students while the control class consisted of 25 students. The instrument of this research is documentation at the time of learning. Against the attitude of students when doing learning. The results of hypothesis testing are obtained for tcount 6.12 and for ttable 1.67425, Ho is rejected and Ha is accepted, so it can be concluded that the application of the spider concept map strategy has an effect on student learning outcomes in social studies subjects for class IV SD Negeri 2 Tanah Abang. The results of the student documentation sheet in the control class by applying the conventional method of the theme book obtained an average calculation result of 51.36, which is a sufficient category. Meanwhile, the experimental class student documentation sheet by applying the spider concept map strategy got an average result of 68.63 good categories.Keywords: Learning Outcomes, Influence, Spider Concept MapAbstract : Penerapan Strategi Peta Konsep Laba-Laba Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas IV SD Negeri 2 Tanah Abang. Penelitian ini dilakukan oleh peneliti bermaksud untuk mengetahui 1) perbedaan yang signifikan hasil belajar siswa kelas IV SD Negeri 2 Tanah Abang yang diajar menggunakan peta konsep laba-laba terhadap hasil belajar 2) Penerapan strategi peta konsep laba-laba terhadap hasil belajar siswa pada mata pelajaran IPS kelas IV SD Negeri 2 Tanah Abang. Penelitian ini mengaplikasikan metode eksprimen yaitu digunakan adalah tes berupa kuisioner soal esai sebanyak 15 soal, dan untuk lember Quasi Experiment Design dengan betuk desain Nonquivalent Control Group Desain. Sampel pada konteks penelitian ini terdiri dari dua kelas, kelas eksprimen yang berjumlah 30 siswa sedangkan kelas kontrol berjumlah 25 siswa. Instrument penelitian ini yaitu dokumentasi pada saat melakukan pembelajaran. Terhadah sikap siswa saat melakukan pembelajaran. Hasil uji hipotesis didapatkan harga thitung 6,12 dan untuk ttabel 1,67425 maka Ho ditolak dan Ha diterima, sehingga dapat disimpulkan bahwa berpengaruh penerapan strategi peta konsep laba-laba terhadap hasil belajar siswa pada mata pelajaran IPS kelas IV SD Negeri 2 Tanah Abang. Adapun hasil lembar Dokumentasi siswa dikelas kontrol dengan mengaplikasikan metode konvensional buku tema didapatkan hasil perhitungan rata-rata 51,36 yaitu kategoti cukup. Sementara itu lembar hasil dokumentasi siswa kelas eksperiment dengan mengaplikasikan strategi peta konsep laba-laba didapat hasil rata-rata kategori 68,63 kategori baik.Kata Kunci : Hasil Belajar, Pengaruh, Peta Konsep Laba-Laba